Enhancing the fracture resistance of carbon fiber reinforced SiC matrix composites by interface modification through a simple fiber heat-treatment process. (November 2016) - Liu, H.T.; Yang, L.W.; Sun, X.; Cheng, H.F.; Wang, C.Y.; Mao, W.G.; Molina-Aldareguia, J.M.
Abstract: A simple method to significantly increase the toughness of carbon fiber reinforced SiC matrix composites is presented. The method is based on the heat treatment of Toray T300 carbon fibers in vacuum, leading to the in-situ formation of carbon coatings on the fiber surface that optimizes the interfacial strength in carbon fiber reinforced SiC matrix composite. The formation mechanism of the in-situ coatings was studied by transmission electron microscopy, and the effects of the in-situ carbon interphase on the interfacial property and fracture resistance of the composites were comprehensively assessed by combining transmission electron microscopy, fiber push-in and macro mechanical testing. The results reveal that the in-situ coating was originated from the pyrolysis of the proprietary sizing of the T300 fibers, that was crystallized during thermal treatment, maintaining a low oxygen content. For this reason, the resulting coating can effectively hinder the interfacial reactions in carbon fiber reinforced SiC composites, and remarkably weaken the composite interfacial shear strength from 105 ± 10 MPa to 30 ± 5 MPa. Due to the introduction of in-situ carbon interphase, the toughness of the carbon fiber reinforced SiC composite increased significantly from 1.7 ± 0.3 MPa m 1/2 to 21.3 ± 0.7 MPa m 1/2, triggered by toughening mechanisms such as crack deflection and fiber pullout.